Peran Pengelolaan Manajemen Sumber Daya Manusia Dalam Meningkatkan Mutu Sekolah Di MTs Muttaqien Takeran Magetan - Fityan Akbar Rizki (Hikamatzu | Journal of Multidisciplinary, 2025)
This activity is based on the ongoing Praktik Pengalaman Lapangan (PPL) process at MTs Muttaqien Takeran Magetan which requires students to write a scientific article. The purpose of this study is to find out how the process of managing human resources (HR) at MTs Muttaqien Takeran Magetan is always supervising in improving the quality of education and always getting achievements in various competitions participated by students and educators from the city level to the national level. The type of research used is qualitative research using data collection through observation, interviews and documentation